SWEET ON THE OUTSIDE BUT NOT ON THE INSIDE -LIQUITAB INJURIES IN A TERTIARY PAEDIATRIC EMERGENCY DEPARTMENT (PED). Issue 12 (23rd November 2015) - Mullen, S; Maney, J; Casey, C
Abstract : Objectives & Background: Following the near fatal aspiration of a liquitab in RBHSC, a review of the department's management of this increasingly common issue was undertaken. The aims of the audit were: 1) Identify the frequency of liquitab injuries 2) Assess the range of injuries caused by liquitabs Methods: The electronic system uses to register and track patients (Symphony) was used to collect the data. Data was reviewed for the years 2012/2013. Cases were included only if the injury was due to a liquitab. Results: 275 cases were identified from the preliminary search. 40 of these were documented liquitab injuries (15% of non-medicinal ingestions). Type of injury : Ingestion – 28/40 (70%) and eye injury – 12/40 (30%). No children had inhalation or skin injury noted. Ingestion –17/28 (60%) of these patients presented with vomiting. Treatment was supportive in all cases. Eye injury – Eye irrigation was carried out 100% – pH was tested 11/12 cases – Corneal abrasion was seen in 2 cases – Ophthalmology were involved in 7 cases (58%) Outcome –95% (38/40) of children were discharged after observation –2.5% admitted (1/40) under ophthalmology –2.5% (1/40) of discharged from triage; described as low risk –12.5% (5/40) had follow up appointments with ophthalmology the following day Explanation of injury: Unsupervised play in 37.5% (15/40) with the remainder not documented.275 cases were identified from the preliminary search. 40 of these were documented liquitab injuries (15% of non-medicinal ingestions). Conclusion: The results highlight the difficulties that children can encounter from liquitab injuries. The colourful nature, "sweet-like" appearance and soft texture of liquitab detergents make them appealing to young children. A key issue was to improve parental awareness. We have achieved this via a national press release through Rospa, (Royal Society of the Prevention of Accidents), BBC news interviews and national press articles.